Measurement and Prediction of Thermo Physical Properties of Binary Liquid Mixtures at Various Temperatures Using McAllister Model - R., Ramesh; Anwaruddin, Hisyam; K., Ramesh (The IJES, 2014)
The purpose of this study conducted in this research was to measure thermo physical properties like Viscosities, η, and Densities, ρ, of 1,4 Dioxane with two hydrocarbons like Bromobenzene and Ethylebenzene at different mole fractions and various temperatures in the atmospheric pressure condition. From the experimental data excess volumes, V E , and deviations in viscosities, Δη, of mixtures at infinite dilutions have been obtained. The measured systems exhibited positive values of V E and negative values of Δη. The binary mixture 1, 4 Dioxane + Bromobenzene show positive V E and negative Δη with increasing temperatures. The outcomes clearly indicate that weak interactions present in mixture. It is mainly because of number and position of methyl groups exist in these aromatic hydrocarbons. These measured data tailored to the McAllister model to derive the binary coefficients. Standard deviations obtained from the fitted outcomes and the calculated data is helpful deliberate mixing behavior of the binary mixtures. It can conclude that in our case, the data found with the values correlated by the corresponding model is very well. The molecular interactions existing between the components and comparison of liquid mixtures were also discussed.